Long-Term Effects of Obstetric Fistula on the Overall Quality of Life among Survivors Who Had Undergone Obstetric Fistula Repair, Central Gondar Zone, Northwest Ethiopia, 2020: A Community-Based Study. (8th February 2022) - Aynalem, Getie Lake; Kassie, Belayneh Ayanaw; Baye, Chernet; Tamiru, Animut Tagele; Anteneh, Kiber Temesgen; Berhe, Aster; Fentahun, Wagaye; Debele, Tibeb Zena; Yirdaw, Birhanu Wubale; Rade, Bayew Kelkay; Enyew, Mihretu Molla
Abstract : Introduction . Childbirth is a special time in the lives of women and families at large. It can also be a time of great tragedy. International reports show that, annually, more than 500, 000 women die from pregnancy and childbirth complications globally. For every woman who dies in childbirth, majorities remain alive, but scarred by permanent disabilities. Obstetric fistula is, without a doubt, the most severe of pregnancy-related disabilities. Objective . This research is aimed at assessing the long-term effects of obstetric fistula on the overall quality of life among fistula survivors in central Gondar zone. Methods . A community-based cross-sectional study was conducted among women who had undergone obstetric fistula repair, 1-4 years after the surgery, in the central Gondar zone. The participants were reached through appointments that were made by the researchers using census approach after having the participants' contact lists (specific residence and cell phone numbers), and research interviews have taken place at the respondents' home or residence using an adapted and validated tool. Data entry and analysis were done using Epi Info version 7 and SPSS version 20, respectively. Results . A total of 182 fistula survivors were interviewed giving a 94.8% response rate. This study indicated that 84.1% (95% CI: 78.8, 89.4) of respondents had a poor overall quality of life. Maternal age (>30 years) (AOR = 3.8, 95% CI: 2.6, 12.3), marital status (divorced survivors) (AOR = 2.7, 95% CI: 1.3, 8.5), and urinary incontinence (AOR = 1.9, 95% CI: 2.4, 11.2) were positive predictors for poor overall quality of life. The majority of fistula survivors, 82.4%, were stigmatized which could make reintegration into the community challenging for them. Healthcare providers have to implement counseling to women for social reintegration and the possibility of gainful societal activities after repairing.